Climate-Smart Mapping and Adaptation Planning (CS-MAP) for Climate-Resilient Coastal Agriculture in Bangladesh: A participatory tool for risk-informed agricultural and water management planning - Salahuddin, Ahmad; Amin, Md. Ruhul; Humaira, Bushra (International Rice Research Institute, 2025)
Climate-Smart Mapping and Adaptation Planning (CS-MAP) is an innovative, data-driven, and participatory planning tool designed to enhance climate resilience in coastal agricultural systems of Bangladesh. The approach integrates scientific climate data with local knowledge to identify climate risks, delineate risk zones, and develop location-specific adaptation strategies. Implemented across ten coastal districts, CS-MAP supports evidence-based decision-making for crop adaptation, water management, land use planning, and livelihood diversification. The tool addresses critical challenges such as salinity intrusion, waterlogging, sea-level rise, and erratic rainfall while strengthening institutional coordination and inclusive planning processes. By supporting scalable, climate-informed agricultural planning, CS-MAP contributes to improved food security, sustainable livelihoods, and long-term resilience in Bangladesh’s vulnerable coastal and polder landscapes.